Pengaruh E-Trust dan Kualitas Aplikasi terhadap Online Booking Intention pada Pengguna Aplikasi TIX.ID Di DKI Jakarta - Rivaldo Pradana Samsuri; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2026)
This research examines how e-trust and application quality affect Jakarta-based TIX.ID consumers' online booking intent (online buying intent). Users trust security and secrecy using E-Trust. This quantitative study collected data from Jakarta-based TIX.ID customers utilising questionnaires. Her 105 randomly chosen respondents were the research sample. The data suggest that E-Trust positively affects TIX.ID users' online booking intentions. The more consumers trust the platform's safety and integrity, the more likely they are to conduct online orders via the app. This research will assist app developers boost consumer trust in the platform and enhance app quality. This is intended to boost Greater Jakarta TIX.ID app users' interest and pleasure while ordering online.